Primary breast cancer biomarkers based on glycosylation and extracellular vesicles detected from human serum - Terävä Joonas; Verhassel Alejandra; Botti Orsola; Islam Md. Khirul; Leivo Janne; Wittfooth Saara; Härkönen Pirkko; Pettersson Kim; Gidwani Kamlesh (Wiley, 2025)
Background
Breast cancer is a very common cancer that can be severe if not discovered early. The current tools to detect breast cancer need improvement. Cancer has a universal tendency to affect glycosylation. The glycosylation of circulating extracellular vesicle-associated glycoproteins, and mucins may offer targets for detection methods and have been only explored in a limited capacity.
Aim
Our aim was to develop an approach to detect the aberrant glycosylation of mucins and extracellular vesicle-associated glycoproteins from human sera using fluorescent nanoparticles, and preliminarily evaluate this approach for the differential diagnosis of breast cancer.
Methods and results
The assay involved immobilizing glycosylated antigens using monoclonal antibodies and then probing their glycosylation by using lectins and glycan-specific antibodies coated on Eu+3-doped nanoparticles. Detection of mucin 1 and mucin 16 glycosylation with wheat germ agglutinin, and detection of the extracellular vesicle-associated CD63 were found to have better diagnostic ability for localized breast cancer than the conventional assays for mucin 1 and mucin 16 based tumor markers when the receiver operating characteristics were compared.
Conclusions
These results indicate that successful differential diagnosis of primary breast cancer may be aided by detecting cancer-associated glycosylation of mucin 1 and mucin 16, and total concentration of CD63, in human serum.